TEHNIK PEMERIKASAAN DAN PENGOLAHAN HASIL ASESMEN - Mujahidin Almubarak; Rahmat Rahmat (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2021)
This study aims to explain the technique of examining the assessment results using the library research research method, namely the library approach by examining books, journals, and other relevant sources. The result of this authorship is a technique of checking the results of the assessment, which is a technique of scoring the raw assessments that have been carried out by educators during the teaching process or the results of examinations. The examination of the results of the assessment carried out is to score in the cognitive, psychomotor and affective domains. The processing of the assessment results is the stage of converting the score into a value using the benchmark reference assessment (PAP) approach or the norm reference assessment (PAN) approach